Online information on dysmenorrhoea: An evaluation of readability, credibility, quality and usability. Issue 19 (20th June 2019) - Lovett, Jordan; Gordon, Candice; Patton, Shelby; Chen, Chen X.
Abstract: Aims and objectives: To evaluate online information on dysmenorrhoea, including readability, credibility, quality and usability. Background: Menstrual pain impacts 45%–95% of women of reproductive age globally and is the leading cause of school and work absences among women. Women often seek online information on dysmenorrhoea; however, little is known about the information quality. Design: This was a descriptive study to evaluate online information on dysmenorrhoea. Methods: We imitated search strategies of the general public. Specifically, we employed the three most popular search engines worldwide—Google, Yahoo and Bing—and used lay search terms, "period pain" and "menstrual cramps." We screened 60 web pages. Following removal of duplicates and irrelevant web pages, 25 met the eligibility criteria. Two team members independently evaluated the included web pages using standardised tools. Readability was evaluated with the Flesch–Kincaid Reading Ease and Flesch–Kincaid Grade formulas; credibility, quality and usability were evaluated with established tools. We followed the STROBE checklist for reporting this study. Results: For readability, the mean Flesch–Kincaid level was 10th grade. For credibility, 8% of web pages referenced scientific literature and 28% stated the author's name and qualifications. For quality, no web page employed user‐driven content production; 8% of web pages referenced evidence‐based guidelines, 32% of web pages had accurate content, and 4% of web pages recommended shared decision‐making. Most web pages were interactive and included nontextual information. Some nontextual information was inaccurate. Conclusion: Online information on dysmenorrhoea has generally low readability, mixed credibility and variable quality. Relevance to clinical practice: Strategies to improve health information on dysmenorrhoea include avoiding complex terms, incorporating visual aids, presenting evidence‐based information and developing a decision aid to support shared decision‐making. Healthcare providers should be aware of the problematic health information that individuals are exposed to and provide education about how to navigate online health information.